Sentiment Analysis of Pospay Application Reviews Using the Bert Deep Learning Method - Mulyati, Erna; Muhammad Ibnu Choldun Rachmatullah; Adri Sapta Firmansyah (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2025)
E-money usage in Indonesia has grown significantly due to increasing internet penetration and smartphone adoption. Digital transactions are becoming more common, with platforms like GoPay, OVO, and Dana leading the market. The government and financial institutions actively support this shift through regulations and initiatives. This study analyzes user sentiment on the Pospay application using the BERT deep learning method, based on 16,760 Google Play Store reviews. To the best of our knowledge, this is the first study to apply BERT for sentiment analysis of Pospay user reviews in Indonesia. The goal is to understand user perceptions and satisfaction. BERT helps capture subtle nuances in reviews, including informal expressions and abbreviations like